Dampak Pornografi Terhadap Perilaku Siswa dan Upaya Guru Pembimbing untuk Mengatasinya - Hariyani, Mulya; Mudjiran, Mudjiran; Syukur, Yarmis (Universitas Negeri Padang, 2012)
Abstract Easily access movies / videos porno allows teens / students freely watch, causing a tendency for teens / students to watch porn movies over and over - again. This leads to difficulty concentrating in learning, resulting in lower student learning outcomes. This study aims to reveal how the effects of pornography on adolescent sexual behavior / student. This study used a descriptive approach. The results showed that the impact of pornography on sexual behavior so students, in this case the tutor is not optimal (low) in the prevention efforts so that students are not accessing pornography